THE ROLE OF BUMDES IN IMPROVING THE ECONOMIC COMMUNITY IN THE VILLAGE OF KEDUNGJAYA, DISTRICT, KEDAWUNG REGENCY, CIREBON - Yanthi, Winda Dwi; Fitralisma, Gian; fata, M. Annisul; Maryadi, Ega; Trimayanti, Imas; Ibrahim, Yusuf (Ann Publisher, 2025)
Abstract: Background. BUMDes is a village business in the form of an institution that management is carried out by the village government and village community in order to encourage improving the economy of village communities or including businesses from the village, by the village and for villages, but in its implementation it still refers to the needs of the community and the potential of the village. Aims. This study aims to determine how the role of BUMDes in Improving Community Economy in Ayuhula Village, Dungaliyo District, Gorontalo Regency. Methods. This research is included in the type of descriptive research with a qualitative research approach. Result. The results of the research show that the active role in the aspect of enhancing the quality of human and community life can be found in this aspect to be able to help socially but economically yet to play a role; In the aspect of strengthening the people's economy as the basis for the strength and resilience of the national economy with BUMDes as its foundation, it is found that BUMDes currently has limited capital so this is quite difficult in doing business expansion; Conclusion. In the aspect trying to realize and develop the economy of the village community, obtained with the limitations owned by BUMDes makes it difficult to develop businesses related to the potential of the village: and in the aspect of helping the community to increase their income so as to increase the income and prosperity of the community, found where there is pessimism from the village government that BUMDes managers have not been able to if the businesses in BUMDes have increased. Implementation. Future plans to develop Micro, Small and Medium Enterprises Medium Enterprises (SMEs) through online advertising are expected to open up job opportunities new jobs and improve the welfare of rural communities. BUMDes has great potential to improve the welfare of village communities, but There needs to be support from the government and the community to overcome various challenges which exists.